Islamic Economy as an Alternative Solution of European Economic Crisis - Didier Raul (International Journal of Science and Society, 2020)
The problem of the economic crisis reoccurred again in the global territory that began with the economic crisis in the country of Greece. The crisis arising from the country's financial deficit due to enormous state debt has an impact on the economic crisis in the European region. This phase of the economic crisis is a manifestation of the failure of the capitalist economic system imposed by western countries. Many economists began to open a discourse to review the existing economic system because it did not provide welfare for the community. Islamic economics starting in the 1970s has begun to be widely studied by various universities in the world, which was eventually implemented with the establishment of the first Islamic Development Bank (IDB) in Jeddah. This then continued with the establishment of an institution for how to distribute the wealth in the financial community (tauzi'ul tsarwah bayna an-ill-fated) with the Islamic economic system. There are 3 (three) principles of Islamic economics which include: the principle of how to obtain assets (al milkiyah), how to manage the ownership of assets that are already owned (tasharuruf fil milkiyah). Ownership of assets in the Islamic economic system consists of balanced individual, state and general ownership. So it is expected that there will be more equitable welfare and of course the existence of moral values ​​for all economic actors.